The inflammatory reaction Of Hepatitis B Virus Patients - AnokNjum, Ali; Abdul-Hassan, Layla Saleh; Hashem , Ihasan A (International Journal of Psychosocial Rehabilitation, 2019)
study aim to estimate immune molecules CD54 & CD74 and TNF-B and IL-8 in patients infected with HBV , A total of (80) seropositive patients for HBV were screened for this study to know level of TNF-B & IL-8 in serum of patient and show expression of CD54 and CD74. Results showed that serum samples were analyzed for IL-8 & TNF-B by ELISA , showed highly significant increases (p<0.05) in serum level of HBV patients as compared with healthy control groups , acute HBV revealed high as well as , increases in serum level of TNF-B significantly(p<0.05) ,while chronic liver disease patients express high increase in serum level of IL-8 significantly(p<0.05).Activated markers study revealed high expression of CD74 & CD45-R in HBV patients as compared with healthy normal groups